2017
DOI: 10.1016/j.bbmt.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Mixed T Cell Chimerism After Allogeneic Hematopoietic Stem Cell Transplantation for Severe Aplastic Anemia Using an Alemtuzumab-Containing Regimen Is Shaped by Persistence of Recipient CD8 T Cells

Abstract: HighlightsClinical outcomes are excellent using an alemtuzumab-containing hematopoietic stem cell transplantation regimen for aplastic anemia.Outcomes are excellent despite prolonged abnormality of the T cell profile.Recipient-derived CD8 T cells shape persistent mixed chimerism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 22 publications
4
37
1
Order By: Relevance
“…Many protocols with lymphodepletion using late dosing have remarkably low rates of GVHD with curative levels of MC. Persistence of recipient CD8 + effector T cells may result in T‐cell MC; a state of MC has been proposed to be protective against GVHD, notably chronic GVHD . Higher cell doses can be given with late alemtuzumab to promote myeloid engraftment without increasing chronic GVHD risk in some non‐malignant disorders in children and adults …”
Section: Timing Of Administration Of Alemtuzumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Many protocols with lymphodepletion using late dosing have remarkably low rates of GVHD with curative levels of MC. Persistence of recipient CD8 + effector T cells may result in T‐cell MC; a state of MC has been proposed to be protective against GVHD, notably chronic GVHD . Higher cell doses can be given with late alemtuzumab to promote myeloid engraftment without increasing chronic GVHD risk in some non‐malignant disorders in children and adults …”
Section: Timing Of Administration Of Alemtuzumabmentioning
confidence: 99%
“…Day 30 ALC and T‐cell recovery (CD4 + and CD8 + ) at Day 100 is more robust when Day 0 alemtuzumab levels are <0.57 μg/mL . T‐cell profiles post‐HCT are profoundly affected by alemtuzumab, with CD4 + being relatively more depleted with an inversion of the normal CD4:CD8 ratio and abnormal T‐cell subset composition . CD4 + and CD8 + T‐cell chimerism were differentially affected as a result, with the former being more commonly of donor origin at 1 year post‐HCT.…”
Section: Immune Reconstitutionmentioning
confidence: 99%
“…However, subsequent studies in older transplant recipients (age > 30) did not show a survival benefit when compared to IST [36]. To reduce toxicity in older patients, newer regimens have incorporated fludarabine with lower-dose cyclophosphamide and with ATG (FCA) or alemtuzumab (FCC), with improved OS [3739]. A CIBMTR analysis of 833 AA bone marrow transplants evaluated the role of ATG source on transplant outcomes, and demonstrated that rabbit ATG (Thymoglobulin, Sanofi, France) results in lower rates of acute and chronic GVHD for MSD transplants, improves survival, and lowers rates of acute GVHD for MUD transplants [40].…”
Section: Transplant-based Therapies For Saa/vsaamentioning
confidence: 99%
“…This is common after transplant and can be converted to full donor chimerism by the use of early donor lymphocyte infusion . The use of either Thymoglobuline ® , Grafalon ® or Campath ® is largely center and country determined because all 3 have been shown to be effective in GVHD prevention but recently the use of alemtuzumab has been more and more extended, especially for non‐malignant diseases …”
Section: Introductionmentioning
confidence: 99%
“…9,17,18 The use of either Thymoglobuline ® , Grafalon ® or Campath ® is largely center and country determined because all 3 have been shown to be effective in GVHD prevention but recently the use of alemtuzumab has been more and more extended, especially for non-malignant diseases. [19][20][21] Given the lack of randomized trials that compare RIC regimen with alemtuzumab vs ATG, we pooled the data of consecutive patients transplanted in 3 centers (2 in France and 1 in London) to specifically analyze the outcome in the unrelated setting for myeloid malignancies.…”
mentioning
confidence: 99%